The Antibacterial Potential of Tannin from Mangosteen pericarp Extract against Lactobacillus casei - Bandaru Rahmatari; Agus Subiwahjudi; Cecilia G.J. Lunardhi (Universitas Airlangga, 2020)
Background: Deep dentinal caries cannot defect the vitality of dental pulp. The microbial populations involved in dental caries are known to be highly complex and variable. Lactobacillus casei is one of the most common carious dentine bacteria. Tannin contained in mangosteen pericarp extract is known to have an antibacterial potency. Purpose. This study aims to determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration of tannin from mangosteen pericarp extract against Lactobacillus casei. Method. This study is an experimental laboratory with a post-test only control group design. Tannin from mangosteen was extracted by 96% ethanol. Lactobacillus casei was diluted into several concentrations using the serial dilution method in the Brain Heart Infusion Broth (BHIB) medium and inserted in several reaction tubes. Every reaction tube was incubated for 24 hours. After being incubated, each concentration was taken and swabbed into Mueller Hinton in the petri dish. Then, every petri dish was incubated for 24 hours and colonies' growth was counted manually in the Colony Forming Unit (CFU). Result. Bacterial colonies' growth at a concentration of 1.56% was 90% less than the positive control group and there was no bacterial colonies growth at the concentration of 3.12%. Conclusion. Tanin from mangosteen pericarp extract has an antibacterial effect against Lactobacillus casei. The MIC of tannin from mangosteen pericarp extract against Lactobacillus casei was at 1.56% and MBC was at 3.12%.